The development of isiZulu as an academic language for the teaching of fundamental concepts in economics - Makhatini, Freedom Nkanyiso (Rhodes University, Faculty of Humanities, School of Languages, 2011)
This thesis looks at language as the medium of all our ideas and sentiments. The thesis represents a position statement regarding the development of isiZulu as an academic language. The field of Economics is used to merely illustrate and support the points that are being made in this work. It is argued that each language is viewed as the means of expression of the cultural heritage of its people, and it remains a reflection of cultural groups who speak that particular language. It is a fact that indigenous African Languages have been, for obvious reasons, blatantly understudied during the apartheid years in South Africa (Rudwick 2004). Languages have market value and the desirability of English as the most important global language today has an effect in most Black learners in South Africa. The study examined the development of indigenous African languages, isiZulu in particular, in Zululand University where ninety percent of students and lecturers are isiZulu first language speakers, and came to a conclusion that there is an urgent need for Black South African students to learn academic subjects through their mother tongues. This would help them in thorough understanding and interpretation of analytic text presented in a foreign language such as English. The study advocates that isiZulu, which is the mother-tongue of many students at the University of Zululand, should be a language for upward mobility to these students, but as the situation stands, isiZulu becomes a neglected or marginalised language since it is not the normal medium of instruction and it is not used for effective communication in their education system.
Keywords: Zulu language -- Study and teaching (Higher) -- South Africa; African languages -- Study and teaching (Higher) -- South Africa; Economics -- Study and teaching (Higher) -- South Africa